Cooperation between the Eurasian Economic Union and the Silk Road Economic Belt: Benefits, Risks, Achievements - E. G. Garbuzarova (Проблемы постсоветского пространства)
The article is devoted to the advantages, risks and achievements of cooperation between the Russian integration project “Eurasian Economic Union” (EAEU) and the Chinese initiative “Silk Road Economic Belt” (SREB). The Eurasian space has a strategic importance for Russia and China, so the political leaders of these global powers decided to join together the EAEU and the SREB for the development, strengthening and expansion of cooperation in the field of economy. On the one hand, the interaction of the two integration projects opens wide opportunities for all participants: economic growth, technological modernization, creation of transport and logistics infrastructure. Russia and China share a common vision of the future foundations of the New World Order. In contrast to the Western model of the organization of international relations on the principle of unipolarity, Russia and China defend the model of a polycentric world order. On the other hand, there are problems that can cause competition between Russia and China. The problems of industrialization of the EAEU member-states, the possible competition between Russian and Chinese goods in the Eurasian market as well as in the field of industrial technology may appear. At the same time, it is important to understand that the interests of Russia and China largely coincide rather than diverge. The interests of both states are not only economic in nature but also related to Eurasian security issues. The first beneficial projects having been signed within the cooperation between EAEU and SREB aim at the development of transport infrastructure and financial assistance to the member-states. Considering the reverent attitude of the post-soviet states to national sovereignty the Chinese project looks the most attractive due to the absence of a supranational body. However, this fact does not exclude the possibility of getting the Central Asian states into excessive financial dependence on China. Meanwhile, the EAEU will help to balance China’s economic and political relations with the Central Asian states.In the context of globalization the cooperation between the EAEU and the SREB could be the first step towards the creation of major international economic structure. Cooperation between the Russian and Chinese projects has enormous potential for effective mutually beneficial development and opens wide opportunities for the participating states. The cooperation of the two projects will strengthen the geopolitical position of Russia and China in Eurasia as opposed to the geopolitical activity of the United States.